THE EFFECTIVENESS OF TRAUMATIC COUNSELING FOR CHILDREN WHO ARE VICTIMS OF NATURAL DISASTERS - Alawiyah, Intan; Ubaidillah, Muhammad; Wahyunengsih, Wahyunengsih (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2022)
This study aims to discuss the effectiveness of traumatic counseling for children victims of natural disasters as a strategy to have a positive psychological impact on children victims of natural disasters. Traumatic counseling has an important role in providing assistance to victims of natural disasters, especially for children. Traumatic counseling helps clients who have experienced such trauma. This research uses a descriptive qualitative approach including, 1) compiling and managing research designs, 2) choosing research subjects, 3) collecting data and analyzing data, 4) presenting research data, and 5) research drawing conclusions. The results showed that traumatic counseling is needed for children affected by natural disasters so that there is no trauma effect for victims of natural disasters. This is because children are more prone to trauma because at a very young age they are more sensitive to imagine the events they experience.